Odpowiedzi

2010-03-17T17:56:35+01:00
1)
2(x+1)=x
2x + 2=x /-2x
2=-x /*(-1)
x= -2

2)
2t-(3t+1)=6
2t + 3t - 1 = 6
5t - 1=6 /+1
5t = 7 /:5
t=1,4

3)
-(4+x)=2(3-x)
4-x=6-2x /-4
-x =2-2x /+2x
x=2

4)
3(y+6)-y+2(y+9)=
3y+18-y+2y+18 =
4y+36



Liczę na najlepsze ;)
2010-03-17T17:57:26+01:00
A)
2(x+1)=x
2x+2=x
2= x -2x
2= -x
x=-2

b)
2t-(3t+1)=6
-1t+1=6
-1t= 6-1
-t = 5
t= -5

c)
-(4+x)=2(3-x)
-4+(-x)=6-2x
-4-x=6-2x
-4-6=-2x+x
-10=-x
x=10

d)
3(y+6)-y+2(y+9)
3y+18-y+2y+18
4y+36

e)
(x-7)-2(3x+5)3
(x-7) -6x -10x3
x-7-6x-10*3
-5x-37
Najlepsza Odpowiedź!
2010-03-17T17:59:34+01:00
2(x+1)=x
2x+2=x
2x-x= -2
x= -2


2t-(3t+1)=6
2t-3t-1=6
-t=7 /*(-1)
t=-7


-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10


3(y+6)-y+2(y+9)=3y+18-y+2y+18=4y+36


( x-7)-2(3x+5)3=x-7-(6x+10)3=x-7-18x-30= -17x-37